Socio-Economic and Mothers' Knowledge of Exclusive Breastfeeding - Yeyen Fujilestari; Rifzul Maulina (Lembaga Pengembangan Kinerja Dosen, 2025)
The coverage of exclusive breastfeeding at the Sikan Community Health Center from 2018-2019 decreased from 50.8% to 28%. Lack of knowledge and the intensive promotion of formula milk are among the causes of the low exclusive breastfeeding rate. The purpose of this study was to determine the relationship between socioeconomic factors and the level of maternal knowledge about exclusive breastfeeding in the Tokorondo Community Health Center Work Area. This study used an analytical method with a cross-sectional approach. The population was 46 mothers with toddlers aged 6-12 months in the Sikan Community Health Center work area. The sample in this study was 36 people, the sampling technique was consecutive sampling. The results showed that exclusive breastfeeding was more common in mothers with low education (60%), unemployed mothers (23.5%), high income (50%), and well-informed (100%). Conclusion: There is a relationship between the level of knowledge and exclusive breastfeeding (p<0.001), while education (p=0.217), occupation (p=1.000), and income (p=0.436) have no relationship with exclusive breastfeeding. It is hoped that health workers can be a source of information about the importance of exclusive breastfeeding for babies up to 6 months of age and after six months of age. After six months, it is continued with the provision of complementary foods while continuing to provide breast milk until the age of 2 years and there is support from the family, especially the husband, as an effort to increase the coverage of exclusive breastfeeding.